2018
DOI: 10.1186/s12883-018-1147-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and perioperative management of intracranial aneurysms in Chinese patients with ischemic cerebrovascular diseases: a case series

Abstract: BackgroundPatients with ischemic cerebrovascular diseases are more likely to suffer from intracranial aneurysms, and their surgical treatment has a growing controversy in this condition. The current case series was aimed at exploring surgical treatment and perioperative management of intracranial aneurysms in Chinese patients with ischemic cerebrovascular diseases.MethodsMinimally invasive surgical approach through small pterion or inferolateral forehead was applied in 31 patients. Anti-platelet drugs were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al's study showed that invasive surgical approach, intraoperative monitoring, effective management of cerebrovascular perfusion, and coagulation can prevent the development of cerebral ischemia and aneurysm rupture. [ 11 ] However, manipulation of the intrasaccular thrombus during coiling can lead to further embolization, [ 12 ] given the risk of intraoperative thromboembolic events, it is possible that the risk of surgery in these patients is higher than in patients with asymptomatic UIA. Further studies are needed before this option can be widely implemented in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al's study showed that invasive surgical approach, intraoperative monitoring, effective management of cerebrovascular perfusion, and coagulation can prevent the development of cerebral ischemia and aneurysm rupture. [ 11 ] However, manipulation of the intrasaccular thrombus during coiling can lead to further embolization, [ 12 ] given the risk of intraoperative thromboembolic events, it is possible that the risk of surgery in these patients is higher than in patients with asymptomatic UIA. Further studies are needed before this option can be widely implemented in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As for patients with ICAS, the target was keeping systolic blood pressure no <90% of baseline blood pressure to avoid the occurrence of relative hypotension and accepted moderately elevated blood pressure, especially when the clipping was performed. 14…”
Section: Study Design and Participantsmentioning
confidence: 99%
“… [101] Usually, the blood pressure can be increased by 20% as appropriate for the specific condition and cerebral perfusion needs, and the target value can be modified by referring to the patient's pre-onset basal blood pressure to avoid hypotension and excessive blood pressure variability. [102] The use of multimodal testing such as transcranial Doppler ultrasound, electroencephalography, and cerebral oxygen to individualize the guidance of blood pressure management, reduce cerebral vasospasm, and improve cerebral perfusion has good clinical application.…”
Section: Management Of Hypertension In Special Types Of Critically Il...mentioning
confidence: 99%